Identification of Flow-Induced Noise Sources on Two-Dimensional High Lift Devices of Commuter Aircraft - Arifin Rasyadi Soemaryanto; Muhammad Fajar; Teuku M Ichwanul Hakim; Sinung Tirtha Pinindriya; Kurnia Hidayat (National Institute of Aeronautics and Space - LAPAN, 2021)
A numerical predictive tool of flow induced noise generated by deployed high-lift devices of commuter aircraft is presented in this paper. The aircraft high-lift devices are consisting of vane and flap component. The aim of this study is to identify the sources of flow induced noise on the wing and flap cross-section of the aircraft. This study is investigated only two-dimensional effects and two configuration of flap deflection. A numerical computation is carried out using a CFD software with Large Eddy Simulation fluid turbulence model and Ffowcs-Williams & Hawkings analogy for acoustic prediction. Several sound receivers have been installed on far-field and near-field region of the wing-vane-flap cross-section of aircraft to measure the sound spectra. It has been identified that on the cavity of wing and vane-flap cross-section has the highest sound pressure level than another region. There is a vortical separation and shear layer which is contributed to the generation of sound emission downward the cross-section